Identification of IS1356, a new insertion sequence, and its association with IS402 in epidemic strains of Burkholderia cepacia infecting cystic fibrosis patients. - Tyler, S D (1996)
Burkholderia cepacia is now recognized as an important opportunistic pathogen in cystic fibrosis (CF) and other compromised patients. Epidemicity among CF patients has been attributed to at least one particularly infectious strain (strain ET12), and both genetic evidence and anecdotal evidence suggest that this strain, currently endemic in Ontario, and those causing an epidemic in the United Kingdom, are indeed the same. Our study was conducted to determine whether there was any association between the presence of various insertion sequence (IS) elements, the cable pilin subunit gene (cblA), electrophoretic type (ET), and ribotype (RT) in a collection of 97 clinical and 2 environmental isolates of B. cepacia. No apparent linkage was found for IS elements IS401, IS402, IS406, IS407, and IS408 with ET or RT. The cblA target, said to be a marker for high infectivity, was detected in 100% (38 of 38) of strains of B. cepacia ET12 and in a single strain of ET13 that differed in a single enzyme allele. A new IS, IS1356, identified during the investigation, was present in 71.7% of all isolates, and 50.7% of these isolates harbored IS1356 as a hybrid IS element inserted into IS402. IS1356 is 1,353 bp in length, and when it is inserted into IS402 it results in a 10-bp duplication at the site of insertion. IS1356 contains one major open reading frame of 1,260 bp coding for a putative transposase which has significant homology to ISRm3 in Rhizobium meliloti (59%) and to an undesignated IS element in Corynebacterium diphtheriae (49%). The IS402-IS1356 element was found exclusively in the epidemic strains from Ontario and the United Kingdom, being detected in 94.7% (36 of 38 isolates) of B. cepacia ET12 isolates. Of the two ET12 isolates found to be devoid of the IS402-IS1356 element, both contained IS1356 unassociated with IS402, one was temporally unrelated to the epidemic, and the other was from a CF patient in a geographic area remote from Ontario and the United Kingdom. It is evident that the IS402-IS1356 hybrid element, the cblA pilin subunit gene, and the allelic suite represented by multilocus enzyme electrophoretic type ET12 may provide useful markers for the epidemic, highly transmissible transatlantic strain isolated in Ontario and the United Kingdom.